Pore Structure and Connectivity of Mixed Siliciclastic-Carbonate Tight Reservoirs in the Palaeogene from Qaidam Basin, NW China - Xin Wang; Jianhui Zeng; Kunyu Wu; Xiangcheng Gao; Yibo Qiu; Tongzhi Lu; Kunkun Jia; Chen Zhang; Juncheng Qiao; Zixin Xue; Qianyou Wang; Xiangye Kong (Geofluids)
The pore structure and connectivity in petroleum reservoirs are controlled in part by their petrological properties. Mixed siliciclastic-carbonate rocks have complex compositions and heterogeneous spatial distributions of the various minerals. As a result, the study of the pore structure and connectivity of mixed siliciclastic-carbonate tight reservoirs has been limited. In this study, methods such as thin section microscopy, X-ray diffraction, X-ray computed tomography, low pressure N2 adsorption, and spontaneous imbibition were adopted to comprehensively analyze the petrological properties, pore structure, and connectivity of the mixed siliciclastic-carbonate tight reservoirs in the upper member of the Xiaganchaigou Formation in the Yingxi Area, Qaidam Basin. The results showed that micrometer-sized pores in mixed siliciclastic-carbonate tight reservoirs are mainly dissolution pores, and that the spatial distribution of the pores is highly heterogeneous. The average pore radius range, average throat radius range, and average coordination number range of micronmeter-sized pores are 2.09~3.42 μm, 1.32~2.19 μm, and 0.48~1.49, respectively. Restricted by the concentrated distribution of local anhydrite, the connectivity of micronmeter-sized pores develops well only in the anhydrite, showing negligible contribution to the overall reservoir connectivity. In contrast, nanometer-sized pores in the mixed siliciclastic-carbonate tight reservoirs are mainly intercrystalline pores in dolomite. The range of nanometer-sized pores diameters is mainly distributed in 1.73-31.47 nm. The pores have a smooth surface, simple structure, and relatively homogeneous spatial distribution. The dissolution of dolomite intercrystalline pores by acidic fluids increases the connectivity of the nanometer-sized pores. This paper presents genetic models for microscopic pore structures and connectivity of mixed siliciclastic-carbonate rocks, making possible the evaluation on the quality of the mixed siliciclastic-carbonate tight reservoirs.